(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study was find out the effect of physical exercises on speed. To achieve this purpose of the study, thirty men kabaddi players studying in the Pachayappa’s College, Chennai, Tamilnadu, India selected as subjects. They were divided into two equal groups. Each group consisted of fifteen subjects. The subject selected for group I were administered with the predesigned schedule of physical exercises for three days a week which was for twelve weeks at a stretch. While the subject of group II were of control group who did not take part in any special training program except for the regular physical education programs as curriculum requirement. Physical exercises were selected as independent variable. All subjects of two groups were tested on speed at prior to and immediately after the training programme by using 50 meters run. The analysis of covariance (ANCOVA) was used to find out the significant different in any between groups on speed. In all the cases, .05 level of confidence was fixed to test the significance which was considered as an appropriate. The results of the study showed that there was significant difference between physical exercises group and control group on speed. And also it was found that there was a significant improvement on speed due to physical exercises.